Alternative trading systems in the corporate bond market - Matthew Kozora; Bruce Marshall Mizrach; Matthew Peppe; Or Shachar; Jonathan Sokobin (Federal Reserve Bank of New York, 2020)
We investigate the trading of corporate bonds on alternative trading system (ATS) platforms. We draw a key distinction between request-for-quote (RFQ) and electronic communication network (ECN) trading protocols, which balance investors' preference for immediacy and anonymity. Trades on ATS platforms are smaller and more likely to involve investment-grade bonds. Trades on ATS platforms are more probable for older, less actively traded bonds from smaller issues and for bonds traded by more dealers where inventory is high. Moreover, dealer participation on ATS platforms is associated with lower customer transaction costs of between 24 and 32 basis points.
Keywords: G14; G23; G28; 330; corporate bonds; TRACE; electronic trading